2012
DOI: 10.3762/bjoc.8.216
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the relative configuration of tropinone and granatanone aldols by using TBDMS ethers

Abstract: SummaryThe relative configurations of tert-butyldimethylsilyl (TBDMS) ethers of all four diastereomers of the aldols of tropinone (8-methyl-8-azabicyclo[3.2.1]octan-3-one), as well as of granatanone (9-methyl-9-azabicyclo[3.3.1]nonan-3-one), were determined from NMR data, and from the observed interconversion of the diastereomers (exo,anti to endo,syn and exo,syn to endo,anti). The exo forms invert to endo isomers in the presence of silica gel. The relative configuration of a new isomer of tropinone aldol acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Crystal structures indicated that the N-methyl in tropinone [27] and N-phenyl in the granatanone derivative [28] display the axial configuration in the solid state. The N-methyl configuration in the crystals depended on the derivative and was determined to be equatorial in cocaine [29] and its salts [30] as well as in phenyltropane [31], tropinone aldols [32,33], tropinone aldol tosylhydrazone [21], and granatanone aldols [34], but axial in scopolamine [35]. In some conformational studies of granatane derivatives by NMR methods [36], the N-methyl stereochemistry remained undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…Crystal structures indicated that the N-methyl in tropinone [27] and N-phenyl in the granatanone derivative [28] display the axial configuration in the solid state. The N-methyl configuration in the crystals depended on the derivative and was determined to be equatorial in cocaine [29] and its salts [30] as well as in phenyltropane [31], tropinone aldols [32,33], tropinone aldol tosylhydrazone [21], and granatanone aldols [34], but axial in scopolamine [35]. In some conformational studies of granatane derivatives by NMR methods [36], the N-methyl stereochemistry remained undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…This correspondence combined with the observed equilibration suggests the thermodynamic control of the reaction and involvement of the interconversion of the competing product conformers in the equilibrium. Because of the bicyclic structure (endo and exo faces) of tropane and granatane derivatives, we propose that the syn-anti isomerization of the aldols takes place through retroaldolization (observed in several instances) [19,22,54] and not by enolization mechanism reported, for example, in the imidazole catalysed isomerization [55,56]. Assuming thermodynamic control, it is reasonable to expect that the experimentally observed dr's should result from weighted contributions of the forms involved in the equilibrium.…”
Section: Computational Study Of the Reactionmentioning
confidence: 92%
“…Moreover, our solventless reaction in the presence of small (ca. equimolar) amounts of water [17] is the only practical method for preparation of the exo,syn isomers [18,22]. Because no chiral additives are present in the reacting mixture, the reaction is diastereoselective but not enantioselective and provides products in the racemic form.…”
Section: Journal Of Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…10,14 Regardless of the method used, lithium enolate or aqueous, the only isomers formed are the exo forms, as shown in Scheme 1. 14 Based on the preliminary report, 13,15 it can be proposed that obtaining reasonable conversion and diastereoselectivity in the water-promoted aldol reactions of the heterocyclic amino ketones 1 and 2 is conditioned by numerous factors, including the following: (i) a tertiary nitrogen atom built into the ketonesan achiral organocatalyst; (ii) water as the source of a strong base facilitating the enolization step; (iii) an aqueous solution as a perfect environment for spontaneous crystallization; (iv) formation of internal hydrogen bonds in the products; and (v) thermodynamic stability of the products formed. Although these factors could be identied, the actual yield and the exo,syn to exo,anti isomer ratio was dependent on the specic amino ketone and aldehyde used, and was difficult to control.…”
Section: Introductionmentioning
confidence: 99%